Infections of Diabetic Foot Ulcers With Methicillin-Resistant Staphylococcus aureus. (March 2015) - Cervantes-García, Estrella; García-González, Rafael; Reséndiz-Albor, Aldo; Salazar-Schettino, Paz Maria
Infected diabetic foot is the most common reason for hospitalization and complications in patients with type 2 diabetes mellitus (DM2). Methicillin-resistant Staphylococcus aureus (MRSA) is frequently isolated from such lesions, and its presence is growing, seriously deteriorating the infected patient's quality of life. The aim of this study was to assess the prevalence of MRSA as well as other microbiota in 100 patients diagnosed with (DM2) and with infected foot ulcers at the Hospital General de Mexico. The main results obtained show a prevalence of Staphylococcus aureus (42%), followed by Escherichia coli (36%) and, in lower percentages, other bacteria. MRSA was predominant (34%), and we conclude that the use of cefoxitin instead of oxacillin as the first-choice antibiotic has an advantage because it is a better inducer of methicillin-resistance expression.